Community participation for sustainable development goals: the localisation process / Mohd Idham Mohd Yusof ... [et.al.]. - Mohd Yusof, Mohd Idham; Yusof, Radduan; Ab Rahman, Farah Adilla; Harsono, Dwi
According to Sustainable Development Goals (SDGs), localisation is pertinent in supporting global agenda implementation. Realising this importance, Malaysia's Ministry of Housing and Local Government (MOHLG) has encouraged local authorities to realign their programmes and activities with SDG-oriented policies. Consequently, a few of the leading local authorities produced their maiden Voluntary Local Review (VLR) in 2021. An essential component of SDGs localisation involves the inclusion of the youth community. This study, therefore, aimed to explore youth community involvement in five different Malaysian regions, focusing on the issues they encountered and the importance of being involved in the localisation process. Interviews with youth representatives indicated that they faced a few institutional and commitment impediments involved with the SDGs.